Respons Tanaman Jagung (Zea mays l.) Terhadap Pemberian Kombinasi Pupuk Anorganik dan Pupuk Organik Fermentasi (Porasi) Kotoran Sapi - Rudi Priyadi; Ade Hilman Juhaeni; Candy Kusuma Dewi (Paspalum: Jurnal Ilmiah Pertanian, 2021)
This study aims to determine the dose combinations of inorganic fertilizers and the fermentation of organic cow dung that respond well to corna. This research was conducted by August to November 2020, in the experimental garden of the Agriculture Faculty, Siliwangi University, Mugarsari Village, Tamansari District, Tasikmalaya City with a height of 360 meters above sea level (m asl). The study used a randomized block design (RBD) with 6 treatments and was repeated 4 times. Dose tested P0 = control (without being given fertilizer), P1 = Poration of cow dung 20 t / ha, P2 = NPK 300 kg / ha, P3 = NPK 250 kg / ha + cow dung poration 5 t / ha, P4 = NPK 200 kg / ha + poration of cow dung 10 t / ha and P5 = NPK 150 kg / ha + poration of cow dung 15 t / ha. The results showed that the application of NPK fertilizer and cow dung could be responded to by corns, with the results of statistical analysis that was significantly different on plant height at 18 DAS, weight of 100 seeds and shelled weight per hectare.